CONTRIBUTION OF HUMAN DEVELOPMENT INDEX TO IMPROVING THE QUALITY OF HUMAN RESOURCES AND ECONOMIC GROWTH - Dharmawan, Donny; Renaldi, Renaldi; Aglis Andhita Hatmawan; Murwani Wulansari; Muhammad Rispan Affandi (Bajang Institute, 2025)
The purpose of this study is to explain how a theory of contribution of human development index to improving the quality of human resources and economic growth. This type of research is literature research that discusses the presentation and contribution of human development index theory to improving the quality of human resources and human development index to economic growth. This research requires secondary data, such as books and journals in answering the contributions of the theories needed. The results of the study show that based on Todaro's theory regarding human development index and improving the quality of human resources have a close relationship. The relationship between human development index and economic growth is reciprocal and complex. Economic growth can support human development through increased income and investment in education, health, and infrastructure.